40. The Xenakis Networked Performance Marathon 2022: An Experiment in Networked Performance Collaboration Inspired by Iannis Xenakis - Iannis Zannos; Martin Carlé; Vasilis Agiomyrgianakis; Takumi Ikeda; Hanako Atake (Meta-Xenakis: New Perspectives on Iannis Xenakis’s Life, Work, and Legacies, 2024)
In this chapter, we provide a summary of the Xenakis Networked Performance Marathon project, a computer music and dance performance marathon comprising sixteen pieces with worldwide live participation over the internet, dedicated to the memory of Iannis Xenakis. The project’s aim was to explore collaborative performance practices using the internet, through the use of alternative protocols and technologies such as UDP-based OpenSoundControl and experimental, low-cost wearable sensors systems for motion capture. We describe the hardware and software used in the project, as well as the original development work required to incorporate these tools in our work setup. We compare various hardware systems employed, focusing on the Zigbee-based Sense Stage system versus a Bluetooth-based PineTime smartwatch-based system. Finally, we outline the pieces performed in this project, giving summaries of their inspiration and objectives. The performances span a wide spectrum of approaches and techniques. They demonstrate the potential of current technology for networked collaborative performance and show its impact on the aesthetic of experimental musical and dance art forms.